TESty – Typing Easier: an innovate device to characterize blood samples. (24th June 2020) - Mourato, C; Martins, D; Teixo, R; Mendes, F
Abstract: Introduction In Portugal there are over 130, 000 regular donors (2 to 4 blood donations/year), data from 2017. These data lead us to approximately 500, 000 donations per year just in Portugal. In addition, we have over 300, 000 transfusions per year that may require more than one unit of blood. All of these units, prior to administration, and all patients before a blood transfusion or even a transplant, must be properly classified regarding their blood type. Currently, the standard (tube) technique requires that at least 8 tubes be used per individual and the card, a device widely used today, requires the use of 1, 5 per individual. It also requires the purchase of expensive laboratory equipment specifically for this purpose. The complex protocol, requiring access to laboratories with specific equipment without any other use (eg card centrifuges) and need to be performed by professionals specialized healthcare providers are the main disadvantages. Objectives Our main goal was to develop a new cost effective and efficient device- TESTy which could allow the evaluation of a higher number of samples discarding the need of any supplementary device or equipment. Methodology A 96-well V-bottom microplate was used as support device. After, an agarose gel and the antibodies serums were soaked in each well according to the specifications of the blood determination test. Results After a six month evaluation, TESty provide the same results as expected and previously tested with the other two techniques available at the market. Conclusion TESty can be revolutionary in the science transfusion world once it allows the screening of 12 samples simultaneously and this fact can save time and resources daily in our laboratories and blood banks. Also, for being a cost-effective product, it can be extended to undeveloped countries and contribute to assure the transfusion safety required.